Associations Between Lower-Body Power, Static Balance, Agility, and 30-Meter Sprint Performance Among Sport Science Students - Ahmad, Alvia; Sulfa, Muhammad; Zulnadila, Zulnadila; Risal, Andi Wirawan; Rahman, Andi Abdul; Sangkalabu, Adelvin; Rismadani, Rismadani (Physical Education, Health and Recreation Study Program, Universitas Insan Budi Utomo, Indonesia, 2026)
Sprint performance is a fundamental biomotor component that plays an essential role in many sports because it reflects an individual's acceleration capacity, movement efficiency, and overall physical performance. Although lower-body power, static balance, and agility are considered important determinants of sprint ability, their relative contributions to sprint performance among sport science students remain insufficiently understood. This study aimed to examine the associations of lower-body power, static balance, and agility with 30-meter sprint performance among sport science students at Cahaya Prima University. A quantitative correlational design was employed involving 16 participants selected through purposive sampling from a population of 43 students. Lower-body power was assessed using the Standing Broad Jump Test, static balance using the Standing Stork Test, agility using the Illinois Agility Test, and sprint performance using the 30-meter sprint test. Data were analyzed using descriptive statistics, Spearman's rank correlation, and multiple linear regression. The regression analysis revealed that lower-body power, static balance, and agility collectively explained 59.7% of the variance in 30-meter sprint performance (R² = 0.597, p = 0.010). Among the variables examined, lower-body power demonstrated the largest standardized regression coefficient, indicating the strongest relative association with sprint performance, although none of the individual predictors reached statistical significance in the partial regression analysis. These findings suggest that improving sprint performance requires not only sprint-specific practice but also training programs emphasizing the development of lower-body power and agility.